THE EFFECT OF SULFURIC ACID AND Averrhoa bilimbi EXTRACT AS CATALYSTS ON FURFURAL YIELD FROM CORN COBS IN THE HYDROLYSIS PROCESS USING MICROWAVE - Fitri, Ayu Chandra Kartika; Widyastuti, Fikka Kartika (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2024)
Furfural is a selective solvent for petroleum that can produce high-quality diesel fuel. Generally, furfural research uses raw materials from corn cobs, but most still use inorganic acid catalysts. Therefore, researchers are trying to find alternative catalysts using environmentally friendly organic acids from Averrhoa bilimbi extract. This research aims to determine the effect of the concentration of sulfuric acid catalyst and Averrhoa bilimbi extract in the hydrolysis process on the quality and yield of furfural and the impact of using microwave heating on the quality and yield of furfural produced. The method used to make furfural is hydrolyzing corn cobs using a microwave heater (400 Watt power) with various sulfuric acid catalyst concentrations (10%, 15%, and 20%) and Averrhoa bilimbi. Observe the number of yields at each time interval of 60, 75, and 90 minutes. The resulting furfural is then analyzed to calculate the yield of each sample and identify furfural compounds using Gas Chromatography-Mass Spectrometry (GCMS). The research results showed that the best furfural yield at a catalyst concentration of 10% H2SO4 with a time of 90 minutes was 14.9632%. In GCMS analysis, the compound peaked on gas chromatography at a retention time of 2.208 with a relative molecular mass of 83.